Mola Hidatidosa Komplit dan Hipertiroid pada Multigravida : Laporan Kasus - Maitsa, Nisrina Ayu; Zulfadli (CV. Jasa Sukses Abadi, 2024)
Hydatidiform mole is an abnormal condition in pregnancy in which some or all of the chorial villi undergo hydrophic degeneration. Hydatidiform moles are classified into complete hydatidiform moles and partial hydatidiform moles. The incidence rate in Indonesia is around 1:80 normal births. Meanwhile, the incidence of partial molars is very rare, the incidence varies between 5:100,000 and 1:10,000 pregnancies. A 23 year old G4P2A1 woman came with complaints of bleeding from the genitals for 2 hours at SMRS. Fresh red blood, bubbles like fish eyes (+) but blood clots (-). Complaints accompanied by abdominal pain and genital pain. The patient was declared pregnant by the midwife. History of trauma (-), infection (-), history of abortion with a distance of ±4 months. Physical examination revealed consciousness compost mentis, BP 113/85 mmHg, pulse 125x/minute, respiration 24x/minute, temperature 36.6 C. Obstetric examination of the abdomen slightly convex, weak, striae (+), tenderness (-), fundal height uterus at the level of the umbilicus, DJJ (-). On inspection, the portio livid was found, the external uterine orifice was closed, the blood flux (+) was inactive. Laboratory examination revealed Hb 9 gr/dl, T3 3.06 nmol/l, T4 236.31 nmol/l, TSH 0.03 uIU/L and β hCG >5000 mIU/ml. Ultrasound shows snowstorm and vesicular pattern. This patient was diagnosed with complete hydatidiform mole and hyperthyroidism. Therapy consists of suction curettage and hyperthyroid medication. The conclusion is that the examination for the patient's diagnosis is sufficient and the therapy given is appropriate.